Sustainable power solutions for next-generation medical devices - Ye Liang; Chi Zhang; Rubing Lin; Junqing Lin; Jishizhan Chen (Materials Today Bio, 2025)
Next-generation medical devices include implantable medical devices (IMDs) and wearables, exemplified by devices such as pacemakers for heart regulation and deep brain stimulators for neurological disorders, which have significantly advanced healthcare by offering critical treatments and improving patient outcomes. However, conventional battery technologies for these devices remain prevalent, and their constraints on longevity, size, and necessity for periodic replacement or recharging pose significant challenges, especially in implantable scenarios, presenting concerns regarding patient safety, healthcare costs, and device reliability. To address these issues, this review investigates alternative energy sources that tap into the intrinsic energy of the human body and delves into a range of promising energy harvesting techniques, including electromagnetic energy harvesting, ultrasound wireless power transfer (US-WPT), energy generation from tissue motion and heartbeats, utilization of body thermal gradients through thermoelectric generators (TEGs), and glucose oxidation within biofuel cells. Each technique is evaluated for its potential to provide a sustainable power source for IMDs and wearables, highlighting distinctive advantages such as dual functionality, enhanced penetration capabilities, access to inexhaustible energy reservoirs from bodily movements, and the biochemical conversion of glucose into electrical energy. Despite their promise, this review also discusses the remaining challenges, future directions, and exciting opportunities associated with these cutting-edge energy harvesting methods, emphasizing the need for multidisciplinary research to overcome current hurdles and unlock new possibilities for self-sustained medical and wearable devices. This review uniquely evaluates energy harvesting techniques through the lens of 'functionally cooperating systems'—emphasizing how synergistic integration of smart materials, adaptive algorithms, and physiological interfaces can overcome fundamental trade-offs between biocompatibility, power density, and clinical viability.